Implementasi Metode Tikrar dalam Kegiatan Menghafal Surat An-Nahl Ayat 125 Mata Pelajaran Al-Qur'an Hadits Kelas XII-I MAN 1 Tuban - Cahyani, Anggie Eka; Zulaikha, Siti; Munawaroh, Mahmudatul; Amin, Fathul (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the implementation of the tikrar method in improving students’ memorization and fluency in reciting the Qur'an in the Al-Qur’an Hadith subject on Surah An-Nahl verse 125 at MAN 1 Tuban. The research used a descriptive qualitative approach with data collected through in-depth interviews with one teacher and two students of class XII-I. Data were analyzed through reduction, display, and conclusion drawing, supported by source triangulation. The findings show that the tikrar method was implemented through gradual repetition of verse segments, emphasizing correct pronunciation and understanding before detailed tajwid correction. The method increased the number of students able to submit memorization in one session, accelerated memorization, and improved focus and confidence. Its effectiveness is supported by repetition as reinforcement and the integration of visual and auditory stimuli. However, students’ basic Qur’anic reading ability significantly influences the outcomes. In conclusion, the tikrar method is effective in strengthening memorization when supported by adequate foundational reading skills